Forms and Functions of Aggression in Early Childhood. Issue 5 (3rd September 2019) - Evans, Spencer C.; Frazer, Andrew L.; Blossom, Jennifer B.; Fite, Paula J.
Abstract : Evidence supports the distinctions between forms (relational vs. physical) and functions (proactive vs. reactive) of aggression; however, little research has investigated these two subtype frameworks simultaneously or by teacher-report in early childhood. We examined the factor structures, interrelations, and longitudinal associations of teacher-reported forms and functions of aggression in young children. Preschool and kindergarten students ( N  = 133; ages 3–6 years; 58.6% male) were rated by their teachers during the spring semester and on two subsequent occasions over the following school year (a three-wave cross-sequential design). Bayesian confirmatory factor analyses and path models were estimated, controlling for covariates and cross-classification of students within classrooms. Correlated two-factor models showed acceptable measurement characteristics for both aggression frameworks. Within and between frameworks, aggression subtypes were highly correlated with one another. Physical aggression showed greater stability than, and was a precursor to, relational aggression, whereas both proactive and reactive aggression were stable and bidirectional. All subtypes—especially reactive and physical aggression—were robustly associated with peer rejection but not with academic performance or depressive symptoms. Results suggest that brief, teacher-reported rating scales can be used to measure forms and functions of aggression during early childhood. However, examination of one framework should elicit questions regarding the other (e.g., to what extent are measures of proactive and reactive aggression capturing physical aggression?), and research following a form-by-function approach may be particularly useful. Given their stability and outcomes, physical, reactive, and proactive aggression may be important targets for screening and intervention in early childhood settings.